Elizabethan Sea-Dogs: A Chronicle of Drake and His Companions - Wood, William, 1864-1947; Johnson, Allen, 1870-1931 (Salt Lake City, UT : Project Gutenberg, 2004)
"Elizabethan Sea-Dogs: A Chronicle of Drake and His Companions" by William Wood is a historical account written during the early 20th century. The book explores the maritime exploits of English sea captains during the reign of Queen Elizabeth I, focusing on figures such as Sir Francis Drake and his contemporaries, referred to as Sea-Dogs. Through detailed narrative and historical analysis, the book aims to illustrate how these individuals contributed to establishing England's naval power and colonial pursuits across the seas. The opening of the book sets the stage for the Age of Discovery by introducing Giovanni Caboto (John Cabot), detailing his voyages that mark the early beginnings of English exploration in America. It highlights the context of 15th-century European exploration, with mentions of Columbus and the significant changes in maritime trade and politics. The narrative discusses Cabot's patent from King Henry VII, allowing him to sail in search of new lands, and tracks his journey from Bristol to the eastern coast of North America. This portion provides an introduction to the themes of exploration, adventure, and the competitive spirit that characterized the maritime endeavors of England during an era of significant historical moment. (This is an automatically generated summary.)
Release date is 2004-07-08
Suzanne Shell, Graeme Mackreth and PG Distributed Proofreaders
Keywords: Great Britain -- History -- Elizabeth, 1558-1603; Great Britain -- History, Naval -- Tudors, 1485-1603; Drake, Francis, approximately 1540-1596 -- Friends and associates